Pyropia yezoensis can utilize CO2 in the air during moderate dehydration - 周伟 何林文 杨芳 林阿朋 张宝玉 牛建峰 王广策 (Chinese journal of oceanology and limnology, 2014)
Pyropia yezoensis, an intertidal seaweed, experiences regular dehydration and rehydration with the tides. In this study, the responses of P. yezoensis to dehydration and rehydration under high and low CO2 concentrations （（600-700）×10^-6 and （40-80）×10^-6, named Group I and Group II respectively） were investigated. The thalli of Group I had a significantly higher effective photosystem II quantum yield than the thalli of Group II at 71% absolute water content （AWC）. There was little difference between thalli morphology, total Rubisco activity and total protein content at 100% and 71% AWC, which might be the basis for the normal performance of photosynthesis during moderate dehydration. A higher effective photosystem I quantum yield was observed in the thalli subjected to a low CO2 concentration during moderate dehydration, which might be caused by the enhancement of cyclic electron flow. These results suggested that P. yezoensis can directly utilize COz in ambient air during moderate dehydration.